Abscisic Acid-Triggered Persulfidation of the Cys Protease ATG4 Mediates Regulation of Autophagy by Sulfide. Issue 12 (9th October 2020) - Laureano-Marín, Ana M.; Aroca, Ángeles; Pérez-Pérez, M. Esther; Yruela, Inmaculada; Jurado-Flores, Ana; Moreno, Inmaculada; Crespo, José L.; Romero, Luis C.; Gotor, Cecilia
Abstract : Hydrogen sulfide negatively regulates the progress of autophagy through persulfide modification of the Arabidopsis AtATG4a protease. Abstract: Hydrogen sulfide is a signaling molecule that regulates essential processes in plants, such as autophagy. In Arabidopsis ( Arabidopsis thaliana ), hydrogen sulfide negatively regulates autophagy independently of reactive oxygen species via an unknown mechanism. Comparative and quantitative proteomic analysis was used to detect abscisic acid-triggered persulfidation that reveals a main role in the control of autophagy mediated by the autophagy-related (ATG) Cys protease AtATG4a. This protease undergoes specific persulfidation of Cys170 that is a part of the characteristic catalytic Cys-His-Asp triad of Cys proteases. Regulation of the ATG4 activity by persulfidation was tested in a heterologous assay using the Chlamydomonas reinhardtii CrATG8 protein as a substrate. Sulfide significantly and reversibly inactivates AtATG4a. The biological significance of the reversible inhibition of the ATG4 by sulfide is supported by the results obtained in Arabidopsis leaves under basal and autophagy-activating conditions. A significant increase in the overall ATG4 proteolytic activity in Arabidopsis was detected under nitrogen starvation and osmotic stress and can be inhibited by sulfide. Therefore, the data strongly suggest that the negative regulation of autophagy by sulfide is mediated by specific persulfidation of the ATG4 protease.